PERLINDUNGAN HUKUM BAGI PEMEGANG MEREK TERHADAP PELANGGARAN MEREK MENURUT UU MEREK INDONESIA - R Eddy Haryadi (Law Department, University of Widya Gama Mahakam Samarinda, 2010)
Brand laws is an exclusive law given by the government to brand owners who listed in General Brand List For certain tome using the brand it self or give to others touse it. Practically, application of this brand laws was not almost suitable with what is definite by laws. So that this mode compesation for brand owners. This action was brand violation. The government have responsibility to protect for application of brand laws. The Problem is how their efforts to protect their property for brand owners and what protectionbthat can given by brand owners to the brand violation. The results conclude that in the brand violation, law may bound others who use the brand without property, this limitation of brand violation which given by laws in order to give protection for owners of their intellectual property especially brand property so that economically or morality it feels protected.